Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1055/s-0037-1603775
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after Robotic-Assisted Thymectomy in Children and Adolescents with Acetylcholine Receptor Antibody-Positive Juvenile Myasthenia Gravis

Abstract: The aim of our study was to describe the long-term outcomes after robotic-assisted thymectomy in a cohort of acetylcholine receptor (AChR)-antibody (Ab)–positive, generalized juvenile myasthenia gravis (JMG). We retrospectively analyzed a cohort of 18 patients (15 females and 3 males) who underwent robotic-assisted thymectomy. At the time of diagnosis, 12/18 patients were prepubertal; the mean age was 9.8 years at the onset of the disease. All patients received therapy with pyridostigmine; additional immunothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…100 However, clinically relevant late effects on the immune system have not been observed, especially in thymectomized jMG patients. 101 Symptomatic therapy. In children and adolescents, the dose of pyridostigmine is calculated as 1-7 mg/kg bw/day, the single dose at the beginning as 0.5-1 mg/kg bw; a maximum daily dose of 450 mg should not be exceeded.…”
Section: Strong Agreementmentioning
confidence: 99%
See 1 more Smart Citation
“…100 However, clinically relevant late effects on the immune system have not been observed, especially in thymectomized jMG patients. 101 Symptomatic therapy. In children and adolescents, the dose of pyridostigmine is calculated as 1-7 mg/kg bw/day, the single dose at the beginning as 0.5-1 mg/kg bw; a maximum daily dose of 450 mg should not be exceeded.…”
Section: Strong Agreementmentioning
confidence: 99%
“… 100 However, clinically relevant late effects on the immune system have not been observed, especially in thymectomized jMG patients. 101 …”
Section: Essential Recommendations (2)mentioning
confidence: 99%
“…In recent studies including 49 children, thoracoscopic thymectomy was also safe for children with juvenile myasthenia gravis (JMG) [143,144]. Two other studies with 9 and 18 children, reported the same results [145,146]. Robotic thymectomy is a safe procedure, complications were low, and without mortality.…”
Section: Thymectomymentioning
confidence: 93%
“…Robotic thymectomy is a safe procedure, complications were low, and without mortality. Thymectomy should be offered as a part of multimodal therapy for treating children and adolescents with acetylcholine receptor antibody-Positive JMG [146].…”
Section: Thymectomymentioning
confidence: 99%
“…Similar to the adult-onset MG, AChR Ab are mostly detected in both ocular and generalized MG [ 55 , 58 ]. Patients with juvenile MG seem to benefit from thymectomy without relevant signs of long-term immunodeficiency [ 59 ]. Ocular MG affects only the external eye muscles, including the levator palpebrae muscle, and manifests with ptosis and diplopia [ 60 ].…”
Section: Clinical Spectrum Of Mgmentioning
confidence: 99%